Pile testing using Osterberg cell - Khoo, Han Sen. (2008)
This dissertation covers pile testing on axially loaded bored piles using the Osterberg cell method, including its working principle, installation procedure, testing method and analysis of results. Reliability, costs, advantages and disadvantages associated to adopting the method are also discussed.